PENGGUNAAN APLIKASI ADOBE PHOTOSHOP DALAM MENINGKATKAN KETERAMPILAN EDITING FOTO BAGI ANAK TUNARUNGU - Silvia Dewi Mega (Jurnal Penelitian Pendidikan Khusus, 2012)
Against the background of this research by the problems that researchers found in a field that is in a class of deaf students in special schools Discourse IX SMPLB Asih who have the ability in the field of computer. The ability of researchers to improve students' skills in the field again with the use of computer applications in the Adobe Photoshop image editing. This study used experimental approach in the form of single subjeck research (the study a single subject), with A-B design and data analysis techniques using graphical visual analysis. From the research results can be seen in the baseline condition is done in six sessions, students are only able to get a score of 18% in the first meeting, After a given treatment in the intervention condition, the ability of the students in taking steps to increase image editing, data showing the stability of the meeting of the seventh to the fifteenth meeting with the highest score of 100% with the steps in doing photo editing skills. Applications can be concluded that the use of Adobe Photoshop to enhance the skills of children with hearing impairment photo editing class IX SMPLB Wacana Asih Padang.